Espacio social y clases sociales en Posadas, Argentina - Gómez, Elías (El Colegio de México A.C., 2021)
The article proposes an analysis of urban social inequalities in the city of Posadas, Argentina, from the Permanent Household Survey for the third quarter of 2017. From an exploratory approach with concepts of Pierre Bourdieu and Norbert Elias, the main dimensions of social space and related social classes are identified. The methodology used includes specific multiple correspondences, hierarchical ascending classification, clustering, and synthesis of local ethnographies. The main objective is a synthesis of urban social inequalities as an initial stage of research; to this synthesis new sources of data, analysis techniques, and localized ethnographies will be incorporated in subsequent stages.